Allergen specific immunotherapy has no influence on standard chemistry and hematology laboratory parameters in clinical studies - Häfner, Dietrich (BioMed Central, 2014)
BACKGROUND: A set of standard clinical chemistry and hematology parameters are usually measured during clinical studies. The major outcome of these standard tests is to control that the drug investigated does not lead to pathophysiological changes in respective organs or blood. In some cases based on scientific rationale such tests may not be needed. In this paper we report on a standard set of clinical chemistry and hematology laboratory parameters measured before and after treatment in three different immunotherapy studies, representing different routes of administration and different formulations. METHODS: Thirteen hematological laboratory parameters and eight clinical chemistry parameters were evaluated from three double-blind, placebo-controlled, randomized, multi-centre, phase III studies. The three studies include one with sublingual immunotherapy (n = 185), one subcutaneous immunotherapy trial with an aluminium hydroxide-adsorbed recombinant hypoallergenic Bet v1-FV (n = 211) and one with pre-seasonal subcutaneous immunotherapy with a 6-grass pollen allergoid (n = 154). RESULTS: Allergen specific immunotherapy with both administration forms and formulations respectively did not show any influence on any of the 21 laboratory parameters analyzed. Few patients had a change in laboratory parameters from within normal range at baseline to either below or above at end-of-treatment. No differences between active and placebo were seen with respect to number of patients with such a change. CONCLUSIONS: This study with different preparations and routes of application indicates that the value of repeated measurements of standard clinical chemistry and hematology parameters during allergen immunotherapy should be discussed further.